The Quality of Selvo E-Modules as Learning Media on The Topic Of Voltaic Cells - Ratna Sari Siti Aisyah; Imas Eva Wijayanti; Siti Aisyah (EduChemia (Jurnal Kimia dan Pendidikan), 2020)
This research is a research and development (R&D) research that aims to find out the development procedures while producing products and the quality of the Selvo E-module application as a learning medium on the topic of voltaic cells. Research and development is carried out by adapting and modifying the Borg & Gall development model trough preliminary study and development stages with limited trials involving the validation of five media experts. Analysis of the data used during development is descriptive analysis and percentage techniques. The sample in this research were students of class XI MIPA Academic Year 2018/2019. The results showed that the development of chemistry e-module has “very good” qualifications for the material aspect with a percentage of 92% and media with a percentage of 97% according to experts. Based on the responses given by students as an assessment sample, the quality of the Selvo E-module application is included in the excellent category with a percentage of 85.24%.